CHEMICAL MODIFICATION EFFECT on THE MECHANICAL PROPERTIES of HIPS/COCONUT FIBER COMPOSITES - Carvalho, Kelly C. C. [UNESP] (2010)
Lignocellulosic fibers from green coconut fruit were treated with alkaline solution (NaOH 10% m/v) and then bleached with sodium chlorite (NaClO(2)) and acetic acid (CH(3)COOH). Alkali-treated and bleached fibers were mixed with high impact polystyrene (HIPS) and placed in an injector chamber in order to obtain specimens for tensile tests. Specimens of HIPS/alkali-treated and bleached coconut fiber composites were tested in tensile mode, and the fracture surfaces of the composites were analyzed by scanning electron microscopy. Untreated, alkali-treated, and bleached coconut fibers were analyzed by scanning electron microscopy and X-ray diffraction. Alkaline treatment was effective for removing the extractives and increasing the roughness of surfaces, while the bleaching treatment intensified the effect of alkaline treatment, while increasing the crystallinity index and surface energy of fibers. Results of tensile tests showed that the addition of 30% alkali-treated and bleached fibers reinforcing the HIPS matrix provided considerable changes in the mechanical properties of composites in comparison with the pure HIPS. on the other hand, chemical treatments were not totally effective for improving the adhesion between the fiber and matrix, as was observed in the analysis of the fracture surfaces of composites materials.